PENGARUH KEBUTUHAN GIZI TERHADAP PERUBAHAN BERAT BADAN IBU HAMIL DI DESA PETIS RT 02 RW 02 KECAMATAN DUDUK SAMPEYAN KABUPATEN GRESIK - Eppy Setiyowati; Desi Emilyati (UNUSA Press, 2017)
Pregnancy caused by changes in body weight of pregnant women, which is not significantly impact on the growth of the fetus in the womb, experiencing anemia and low birth weight. The purpose of this study analyzed the nutritional needs of pregnant mothers to changes in maternal and fetal body weight in the Village District of RW 02 Petis Duduk Sampeyan Gresik. Analytical study design with cross sectional study design. The population is all pregnant women in the village of RT 02 RW 02 Petis Sitting Sampeyan District of Gresik by 33 people. Sampling sampling techniques with simple random sampling. The instrument uses observation. This variable is the nutritional needs of pregnant women and changes in maternal and fetal body weight. Data were analyzed with the Mann-Whitney test with α = 0.05. The result showed the majority (66.7%) of respondents need good nutrition. Aswell as the vast majority (66.7%) of respondents normal weight. It can be concluded that there is influence the nutritional needs of pregnant mothers to changes in maternal and fetal body weight in the Village District of RW 02 Petis Sitting Sampeyan Gresik. More nurses can improve the promotion program to improve maternal and fetal body weight through promotion and education in local communities about the importance of maternal and fetal weight.